Media Pembelajaran Interaktif Sebagai Upaya Pemanfaatan Limbah Kain dan Pakain Dalam Lokakarya Daring Kolase Fesyen - Anandhia Sifa Tyana, Cynthia; Despriliani, Ririn (Program Studi Pendidikan Seni Rupa FBS UNJ, 2023)
This research aims to increase public awareness to take part in preserving the environment, by processing fabric and clothing waste into works of art using the fashion collage method. As well as developing people's skills and creativity, as well as knowing the right methods and techniques to produce a fashion collage work. This research uses descriptive qualitative methods. The data collection techniques used are through observation, interviews, questionnaires, literature, documents and documentation. The work is assessed based on the participant's creativity and skills using Brent G Wilson's modified assessment table. The research results show that the participants' ability to create fashion collages for Zero Waste Indonesia Instagram social media followers in the 20-30 year age range needs to be further developed so that the research results in the form of interactive learning media and syllabi can be implemented by many groups and become a workshop activity that can be recommended as an artistic activity in an effort to utilize fabric and clothing waste.